Collaborative Transdisciplinary Research, Knowledge Sharing and Governance for Disaster Prevention and Mitigation - Butt, Anosh Nadeem; Dimitrijević, Branka (Transdisciplinary journal of engineering & science, 2025)
Considering a range of possible natural and anthropogenic hazards and socio-economic disruptions, the article hypothesis is that the planning of their prevention and mitigation requires transdisciplinary collaboration of science, governance organisations, affected population, and civil society. The literature review enabled identifying types and causes of disruption threats, their scale, governance approaches and recommendations for collaboration in transdisciplinary research, knowledge sharing and governance. Qualitative analysis of the recommendations given in the above studies confirms validity of the above hypothesis. The findings indicate the significance of developing knowledge and skills needed for effective transdisciplinary collaboration. The research value is in providing evidence related to the need for building capacities and capabilities for transdisciplinary collaboration in science, at all levels of governance, and in communities.